Origin of Fe-Mn ± Si layers associated with the Permian volcanic-hosted massive sulphide deposits in the Tasik Chini district, Peninsular Malaysia. (1st May 2020) - Basori, Mohd Basril Iswadi; Zaw, Khin; Davidson, Garry J.; Meffre, Sebastien; Large, Ross R.
Graphical abstract: Highlights: The Fe-Mn ± Si layers at the VHMS deposits in Tasik Chini were formed by chemical precipitation. Sources of such layers were mainly chemical components with minor detrital materials. These layers were formed due to the seafloor-hydrothermal activity associated with hydrothermal vents. Abstract: The volcanic-hosted massive sulphide (VHMS) deposits in the Tasik Chini district, Peninsular Malaysia are hosted in Permian volcano-sedimentary rocks and are composed of Fe-Mn ± Si layers which occur stratigraphically above the ore bodies. The oxide layers are 1 cm to 2 m thick, and occur discontinuously throughout the Bukit Botol deposit, whereas layer of oxides up to 10 m thick occurs continuously over a strike length of over 50 m at the Bukit Ketaya deposit. Their mineralogy is dominated by hematite ± (quartz ± barite ± magnetite ± pyrite ± clastic components), and commonly exhibit massive iron-silica banding to microbreccia-like textures. The Fe-Mn ± Si layers from the Bukit Botol and Bukit Ketaya deposits generally have high Si, Fe, Mn and base metals contents, various proportions of Al, Zr and Ti, and high levels of Ba, As, U and V. Such mineralogical and geochemical concentrations and other geological suggest that the associated Fe-Mn ± Si layers were deposited by the mixing of mainly chemical components and to a smaller degree detrital components in a local submarine environment due to hydrothermal activity on the seafloor.